Semiotics of Da’wah in the Sang Pencerah Film - Rizki Azis Abdullah; Umi Halwati; Nawawi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
The film always tells hidden realities with certain characters and symbols. The characters and symbols represent the story or the meaning that the audience will achieve. As an industry, film in Indonesia was dominated by the horror genre. However, in 2010, Ayat-Ayat Cinta film marked the success of the religious genre, especially those that tell historical figures in the Islamic world. The Sang Pencerah film, released in 2010, is a religious film directed by Hanung Bramantyo. It is based on the true story of the founder of Muhammadiyah, KH Ahmad Dahlan. Therefore, this film is a worthy research object to examine the representation of the da’wah methods in it. This study uses a qualitative research method by applying Charles Sanders Pierce's semiotic analysis, which focuses on signs, sign references and sign users. Data collection techniques in this study were carried out through documentation techniques by analyzing scenes and dialogues in scene footage in the film. The results of this study indicate that the method of da’wah in the Sang Pencerah refers to the Qur'an, especially Surah an-Nahl verse 125, which includes the bil hikmah, bil mau'idhah hasanah, and bil mujadalah methods. The dominant da’wah method in this film is the bil hikmah method.